Causality Between High-Performance Work Systems and Organizational Performance - Shin, Duckjung; Konrad, Alison M. (Journal of management, 2017)
Previous researchers have questioned whether the association between high-performance work systems (HPWS) and organizational performance indicates causality. Strategic human resource management theories, including the resource-based view of the firm and the behavioral perspective, have provided explanations linking human resource management practices to organizational performance. We add arguments based upon general systems theory to suggest a more complex relationship where performance provides feedback on HPWS in the form of information and resources. This feedback generates both the data and the slack resources needed to support an adaptive process of HPWS implementation. We test the causal associations between HPWS and performance using a large longitudinal data set with three time points. Findings showed that past HPWS positively contributes to later productivity as well as the reverse. The reciprocal relationship supports the need to extend strategic human resource management theory by considering productivity as an antecedent as well as an outcome of human resource management practices.